Demenca - Flaker, Vito (Socialno delo, 2022)
Dementia is often the ultimate argument for the need of institutions. However, dementia is not a "disease" that would need an institutional care, and institutions are not an environment of decisive advantage, and the placement in an institution is not the result of a "deterioration" of the state – it is a consequence of the discontinuity of the system, the lack of intensive services in the community, the "drama of institutionalisation" accompanied by reification of human beings and encouraged by the quest for profit. Quite the contrary, institutions can be described as a "machine of oblivion", a foundation of alienation, passivation and intensification of the very difficulties that are usually attributed to the disease process. On the basis of this critique, the author sketches specific elements of deinstitutionalisation in the case of dementia and proposes a heuristic theorem for the research and action in this field. The transition to the community means transforming the modelling of dementia, providing a safe space, adequate intensity of support, a conjunction of informal care and professional interventions, enabling alternative subjectivity and new solidarity. Research and action in the field of dementia should stem from the life-world of so labelled people, and transversely address the variety of plateaus of action. It should focus on the equally transversal phenomena of supplanting the loss of subjectivity and territorial insertion, while also addressing the more fundamental issues of the bifurcation of contemplative and action identity.
Keywords: action identity; dejavnostna identiteta; heuristic model; hevristični model; subjectivity; subjektivnost; total institution; totalna ustanova